Associations between Parents' Negative Talk about Aging and Young Adults' Negative Affect and Efficacy Related to Aging. Issue 4 (2nd October 2022) - Gasiorek, Jessica; Fowler, Craig
ABSTRACT: Guided by the communicative ecology model of successful aging, this study examined the relationship between the frequency of parents' negative talk about aging (i.e., complaints about age and use of age-based excuses) and young adult children's negative affect and efficacy about aging. It also investigated the degree to which a family's general tendency to engage in open communication affected these outcomes. Cross-sectional survey data indicated that the frequency of mothers' and fathers' complaints about aging (as reported by young adults) predicted young adults' negative affect and efficacy related to aging, respectively. The relationship between mothers' use of age excuses and young adults' negative affect about aging was moderated by their families' tendency to engage in open communication.